2023
DOI: 10.1002/ange.202219048
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Active Sites Formed on Cobalt Oxyhydroxide in Glucose Electrooxidation

Abstract: Transition‐metal‐based oxyhydroxides are efficient catalysts in biomass electrooxidation towards fossil‐fuel‐free production of valuable chemicals. However, identification of active sites remains elusive. Herein, using cobalt oxyhydroxide (CoOOH) as the archetype and the electrocatalyzed glucose oxidation reaction (GOR) as the model reaction, we track dynamic transformation of the electronic and atomic structure of the catalyst using a suite of operando and ex situ techniques. We reveal that two types of reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Zhu et al have investigated the electrooxidation of glucose to formate on cobalt oxyhydroxide (CoOOH) electrode, in which, operando spectroscopies and theoretical calculations were combined to reveal two types of reducible Co 3+ ‐oxo species as the active sites in CoOOH for glucose electrooxidation. This research provides new insights into the study of active sites and reaction mechanisms of metal electrodes in the electrorefining of biomass 139 . In addition, a low‐cost and high‐efficiency strategy for hydrogen production was proposed by Wang and coworkers, similar to the method proposed in Figure 8, using a system of indirect electrocatalytic oxidation of glucose, in which the anode first electrocatalytically oxidizes Cu(I) to Cu(II), and then Cu(II) oxidizes glucose to gluconic acid, while Cu(II) is reconverted to Cu(I) to achieve cycle 140,141 …”
Section: Anodic Electrocatalytic Oxidationmentioning
confidence: 96%
“…Zhu et al have investigated the electrooxidation of glucose to formate on cobalt oxyhydroxide (CoOOH) electrode, in which, operando spectroscopies and theoretical calculations were combined to reveal two types of reducible Co 3+ ‐oxo species as the active sites in CoOOH for glucose electrooxidation. This research provides new insights into the study of active sites and reaction mechanisms of metal electrodes in the electrorefining of biomass 139 . In addition, a low‐cost and high‐efficiency strategy for hydrogen production was proposed by Wang and coworkers, similar to the method proposed in Figure 8, using a system of indirect electrocatalytic oxidation of glucose, in which the anode first electrocatalytically oxidizes Cu(I) to Cu(II), and then Cu(II) oxidizes glucose to gluconic acid, while Cu(II) is reconverted to Cu(I) to achieve cycle 140,141 …”
Section: Anodic Electrocatalytic Oxidationmentioning
confidence: 96%
“…Unlike conventional thermal catalysis that uses high-temperature or high-pressure reaction conditions, electro-catalysis systems typically use ambient conditions and avoid the addition of chemical reducing/oxidizing agents which makes regulation of reaction rates relatively simple. Electro-catalytic hydrogenation (ECH) has a long and rich history, 74 and although the electrochemical oxidation of sugars, especially glucose has gained attention, 75,76 electro-catalytic hydrogenation of glucose still remains a challenge. 77 In this context, electrocatalytic production of sorbitol from glucose has been explored.…”
Section: Catalytic Conversion Of Glucose To Sorbitolmentioning
confidence: 99%
“…4,129 These transition metal hydroxyl oxides can also be directly synthesized for the catalytic conversion of glucose. For example, Zhu et al 130 reported the electrocatalytic oxidation of glucose by CoOOH to obtain formate. They suggested that the hydroxyl groups adsorbed by Co 3+ ions (μ 1 -OH-Co 3+ ) are responsible for the oxidation process and that the formation of dicobalt ion-bridged lattice oxygen (μ 2 -O-Co 3+ ) for the catalytic dehydrogenation is the key step (Fig.…”
Section: Transition Metal-based Catalystsmentioning
confidence: 99%